Proposing a new framework for service oriented architecture adoption - Niknejad, N. (Institute of Electrical and Electronics Engineers Inc., 2016)
The development of integrated Information Technology (IT) services and infrastructures in organizations is of high importance since many errors occur due to the fact that non-integrated nature of organizations result in the loss of cost-efficiency and agility. Service Oriented Architecture (SOA) has been proved to be a significant integrated paradigm in many sectors including healthcare, banking, education, etc. Lack of a theoretical framework that clarifies factors influencing SOA adoption in organizations makes a significant research problem that needs more investigations. Therefore, the main purpose of this paper is to propose a framework by integrating Technology-Organization-Environment (TOE) and Human-Organization-Technology fit (HOT-fit) frameworks to investigate the most important factors in making decisions to adopt SOA technology in organizations. Undoubtedly, the proposed framework assists decision makers to facilitate the process of adopting SOA in organizations. Â© 2016 IEEE.